1999
DOI: 10.1007/s004410051333
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of spatial buffering of glutamate in developing rat retinae are mediated by the Müller cell glutamate transporter GLAST

Abstract: The patterns of expression of the glutamate transporter GLAST were compared with the patterns of uptake of exogenous D-aspartate, which is a substrate for all glutamate transporters. At postnatal day 0, fine radial processes and end feet of presumptive Müller cells were weakly immunoreactive for GLAST. At postnatal day 3, intense labelling was associated with astrocytes enveloping newly formed blood vessels on the vitread surface of the retina. Between postnatal days 7 and 10, there was a rapid increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 30 publications
4
70
1
2
Order By: Relevance
“…Müller cells are the glial cells in the retina and assumed to have a considerable role in osmolarity regulation of the retinal microenvironment, since they contribute to the homeostasis of low molecular-weight molecules to protect the retinal neurons from excitotoxicity. 45) Earlier studies showed the transport activity of taurine, the expression of taurine transporters, such as TAUT, GAT1 and GAT3, and high accumulation of taurine in Müller cells, 27,[46][47][48] implying the key role of Müller cells in regulating osmolarity at the retinal ECF. Studies using an in vitro Müller cell model, a conditionally immortalized rat Müller cell line (TR-MUL5 cells), 49,50) suggested that Müller cells are involved in carriermediated taurine transport in an Na + -and Cl − -dependent manner, with a K m value estimated to be 37.9 µM, similar to that of TauT.…”
Section: Role Of Taurine Transport In Cell Vol-ume Regulation In the mentioning
confidence: 99%
“…Müller cells are the glial cells in the retina and assumed to have a considerable role in osmolarity regulation of the retinal microenvironment, since they contribute to the homeostasis of low molecular-weight molecules to protect the retinal neurons from excitotoxicity. 45) Earlier studies showed the transport activity of taurine, the expression of taurine transporters, such as TAUT, GAT1 and GAT3, and high accumulation of taurine in Müller cells, 27,[46][47][48] implying the key role of Müller cells in regulating osmolarity at the retinal ECF. Studies using an in vitro Müller cell model, a conditionally immortalized rat Müller cell line (TR-MUL5 cells), 49,50) suggested that Müller cells are involved in carriermediated taurine transport in an Na + -and Cl − -dependent manner, with a K m value estimated to be 37.9 µM, similar to that of TauT.…”
Section: Role Of Taurine Transport In Cell Vol-ume Regulation In the mentioning
confidence: 99%
“…Detection of D-aspartate uptake was carried out according to our standard methods. [28][29][30] Briefly, testes were removed from rats as described and immediately dissected to remove the capsule around the testis. Small (,2 mm diameter) pieces of tissue were then dissected from each testis and placed into oxygenated physiological media (Ames media; Sigma, Castle Hill, NSW, Australia) or Ames media containing 20 mmol l 21 D-aspartate, at 35 uC for 30 min.…”
Section: Transport Studiesmentioning
confidence: 99%
“…Antibodies against NHERF1 and NHERF2 (Kanjhan et al, 2006), GLAST (Pow and Barnett, 1999), and GLT1b (Reye et al, 2002) have been described previously. Antibody specific for ezrin (residues 362-585 of human ezrin, GenBank ™ accession number NM_003379) was purchased from Zymed Laboratories (San Francisco, CA, USA).…”
Section: Antibodiesmentioning
confidence: 99%